Is The Conditionally Constitutional Doctrine Constitutional? - Oktavinanda, Pramudya A. (UI Scholars Hub, 2018)
Under the Conditionally Constitutional Doctrine, the Indonesian Constitutional Court may declare that a provision of a statute is constitutional if it is read in a way described by the Constitutional Court. In practice, this doctrine allows the Constitutional Court to create new legal norms that might not be covered or even considered in the reviewed statute. The main question is: does the Constitutional Court have any legitimate reasons to use such doctrine? This is especially crucial because the Indonesian House of Representatives once banned the doctrine through amendment to Law No. 24 of 2003 on Constitutional Court in 2011 and shortly thereafter, the Constitutional Court declared that the amendment is unconstitutional. In this article, I will discuss the validity of the Conditionally Constitutional Doctrine through the lens of various theories of legal interpretation, and further conclude that given the nature of judicial review process, attempting to answer the above question from the perspective of traditional legal interpretation theories would not be fruitful. Instead, I would recommend using a pragmatic approach in dealing with the existence of the doctrine and offer certain aspects that can be further pursued by Indonesian legal researchers in order to improve the use of such doctrine.